2022
DOI: 10.21037/atm-22-845
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis and laboratory experiments reveal potential critical genes and regulatory mechanisms in sepsis-associated acute kidney injury

Abstract: Background Sepsis-associated acute kidney injury (SA-AKI) is one of the most frequent and serious complications of sepsis. However, the transcriptional regulatory network of the pathophysiological mechanism of the kidney has not been revealed. This study identified new mechanisms in SA-AKI using bioinformatics analyses and laboratory-based experiments. Methods We performed transcriptomic profiling of mouse kidneys after cecal ligation and puncture (CLP) to mimic clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…It is well known that the proximal tubule has the significant capacity for repair after damage, such as hyperglycemia, inflammation and oxidative stress. [ 27 ] In contrast to the PT, the proportions of other nephron segments exhibited varying changes followed by B4 treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the proximal tubule has the significant capacity for repair after damage, such as hyperglycemia, inflammation and oxidative stress. [ 27 ] In contrast to the PT, the proportions of other nephron segments exhibited varying changes followed by B4 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we performed DEG analysis on PT epithelial cells by comparing the DKD group with both WT and B4 treatment (Figure 3F), and found that upregulated early growth response 1 (Egr1), the injury marker Spp1 promotes the attracting immune cells, including leukocytes, macrophages, and T cells, [ 27 ] and the expression levels of spliceosome regulator serine/arginine‐rich splicing factor (SR) were inhibited in the DKD group, including Srsf2 , Srsf3 , Srsf5 , Srsf6 , Srsf7 and Srsf11 . Among of them, the SR gene upregulated in PT cells by B4 treatment, Srsf5 , that is associated with glucose metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, mmu-miR-7,212-5p-Hmox1 in iron death has been demonstrated as a significant RNA regulatory pathway implicated in the pathophysiological process of SA-AKI in a mouse model of septic AKI. The promotion of AKI development by m 6 A RNA methylation alteration in SA-AKI has been shown (84). A growing number of studies in recent years have revealed that ncRNAs, particularly microRNAs (miRNAs), are connected to AKI (85).…”
Section: Sa-akimentioning
confidence: 99%
“…Furthermore, the role of the RNA m 6 A modification in many biological processes and diseases has been elucidated in the past decade; these processes include autophagy, cell proliferation, stem-cell renewal and differentiation, and the diseases include tumorigenesis, and cardiovascular diseases [139,146,148,149]. In the past three years, several studies have shown that RNA m 6 A marks are involved in the regulation of ferroptosis and thus affects the progression of diseases such as tumor growth and acute kidney injury [133,150,151] and that m 6 A modification regulators used in combination with ferroptosis-related genes can be diagnostic or prognostic markers for tumors in humans [130,[152][153][154][155]. Multiple m 6 A modification regulators have been shown to be aberrantly expressed in various types of tumors, and a prediction model comprising these regulators and ferroptosis-associated genes has been shown to effectively reflect the progression and prognosis of these tumor patients [23,[156][157][158][159].…”
Section: The Rna M 6 a Modification In Ferroptosismentioning
confidence: 99%